2008
DOI: 10.1016/j.jstrokecerebrovasdis.2007.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Steep Increase in Late Midlife Stroke Occurrence among US Men

Abstract: Background-Data on recent stroke prevalence rates among middle-aged men in the United States indicate that men aged 55 to 64 years are 3 times more likely than men aged 45 to 54 years to have experienced a stroke. We aimed to determine potential risk factors that may contribute to this steep increase in late midlife stroke occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Most studies found an association between younger age and headache at stroke onset. 4,[22][23][24]26,39,43,47 In a prospective study of first ever ischemic stroke, 12.2% of those younger than 50 developed HAIS, compared with 8.5% of those older than 50 (p < 0.002). 31 In another population, 45.8% of younger patients (average age 42) developed HAIS vs 20.2% of older patients (average age 75, p < 0.05).…”
Section: Influence Of Age On Haismentioning
confidence: 99%
“…Most studies found an association between younger age and headache at stroke onset. 4,[22][23][24]26,39,43,47 In a prospective study of first ever ischemic stroke, 12.2% of those younger than 50 developed HAIS, compared with 8.5% of those older than 50 (p < 0.002). 31 In another population, 45.8% of younger patients (average age 42) developed HAIS vs 20.2% of older patients (average age 75, p < 0.05).…”
Section: Influence Of Age On Haismentioning
confidence: 99%
“…This condition frequently leads to premature coronary, cerebral or peripheral vascular impairments [16][17][18][19]. For that, this author firstly proposed the ''homocysteine hypothesis of atherosclerosis''.…”
Section: Cardiovascular Disordersmentioning
confidence: 99%
“…Many clinical and epidemiological studies have demonstrated a positive correlation between homocysteine (Hcy) plasma levels and cardiovascular disorders (4,5), leading to the general conclusion that Hcy is a prothrombotic factor (6)(7)(8). However, the mechanism(s) through which elevated circulating levels of Hcy promote vascular disease and thrombosis is still unclear (9).…”
mentioning
confidence: 99%